PENGARUH SUHU DAN LAMA WAKTU PENYANGRAIAN TERHADAP MASSA JENIS BIJI KOPI ROBUSTA MENGGUNAKAN MESIN ROASTING TIPE HOT AIR - Mafaza Kanzul Fikri; Trapsilo Prihandono; Lailatul Nuraini (JURNAL PEMBELAJARAN FISIKA, 2021)
Abstract: An important stage that will determine the quality of ready-to-consume coffee is roasting. This method has been developed and used to obtain the best and specific quality of coffee brewing. In addition to the method used, the type of coffee greatly influences the quality characteristics of the brewed coffee produced. Coffee beans will not have a high commercial value before being subjected to a roasting process for the formation of the best aroma and taste. Roasting is a combination of time and temperature that changes the structure and chemical properties in coffee beans through the pyrolysis process. Even high-quality coffee beans cannot have maximum aroma and flavor if the roasting process is not done properly. This research uses a roasting machine type Hot Air Roasting or with other names Air Roasting is a different roasted coffee method. Coffee roasting process is not on the surface of the roaster but in the air, this coffee roasting method was introduced by Michael Sivetz, a chemical engineer and consultant of the world coffee industry. Based on the results of this study that the decrease in density discussed in the previous paragraph shows that the longer the roasting, the weight of coffee will decrease because the water content in coffee beans has begun to decrease. This shows that the longer the coffee beans are roasted, the better the results of heating. This research process uses a hot air type roasting machine. Hot water is one type of roasting machine that is good and efficient, because the heating carried out by the machine uses electrical energy. The final results obtained in this study the temperature continues to rise but the density decreases. This shows the inverse relationship between temperature and density of coffee and the best roasting results and can be used for brewing robusta coffee at 200 ° C in 15-20 minutes. Keywords: Hot Air Roasting, Robusta Coffee